G460(P) Treatment with a single bolus dose of cholecalciferol does not improve HBA1C levels in a cohort of paediatric patients with type one diabetes. (27th April 2016) - Perchard, R; Magee, L; Mughal, Z; Ehtisham, S; Campbell, J; Ainsworth, S; Marshall, M; Bone, M; Doughty, I; Whatmore, A; Stevens, A; Clayton, PE
Abstract : Background: Intensive glycaemic control in type one diabetes (T1D) reduces progression of complications (DCCT and EDIC). In clinical practice, glycosylated haemoglobin (Hba1c) levels reflect control. Previous studies show that higher 25(OH)D3 levels are associated with lower Hba1c (US SEARCH study). However, there are limited interventional trials assessing the effect of cholecalciferol on Hba1c. Aims. 1. To assess the baseline 25(OH)D3 status in a paediatric cohort of patients with T1D. 2. To determine the effect of cholecalciferol administration on Hba1c. Methods: Children with T1D attending routine clinic appointments from February to April 2011 had blood samples taken with consent, and patients with a 25(OH)D3 level <20ng/ml were treated with a one-off stat cholecalciferol dose of 100 000 (2–10 years) or 160 000 (>10 years) units. Hba1c levels from the year preceding treatment and the year after treatment were recorded. Results: Vitamin D levels were obtained from 51 patients (30 male, 21 female). 35 were Caucasian, 11 South Asian and 5 from other ethnic groups. 42 subjects were vitamin D deficient, but 2 were excluded from the analysis (one moved away, one was non-compliant). All South Asian patients were vitamin D deficient, with mean 25(OH)D3 of 11.2 ng/ml. In Caucasians, there was a negative relationship between baseline 25(OH)D3 level and HbA1C (r= –0.484, p < 0.01), but not in South Asians. In treated patients, paired t tests showed no significant difference in mean Hba1c at 3 months (t=1.010, p 0.328) or at 1 year (t=-1.173, p = 0.248) before and after treatment. One way ANCOVA, controlling for age, gender, ethnicity, BMI and diabetes duration showed no difference in change in Hba1c level between those treated and not treated, at 3m and at 1 year before and after treatment. Conclusion: We confirmed a high prevalence of vitamin D deficiency in this clinic cohort of children with T1D, and found a negative relationship between baseline 25(OH)D3 level and HbA1C in Caucasians. However, in patients treated with a stat dose of cholecalciferol there was no effect on Hba1c. Further studies with larger sample sizes, and using maintenance 25(OH)D3 therapy rather than stat therapy are required.